Physical fitness, cardiovascular and musculoskeletal health, and occupational performance in firefighters - Ras, Jaron; Smith, Denise L.; Kengne, Andre P.; Soteriades, Elpidoforos S.; Leach, Lloyd (Frontiers in Public Health, 2023)
Introduction: To perform their work efficiently and safely, firefighters should maintain all aspects of physical fitness. Cardiac-related incidents are the leading cause of duty-related deaths in firefighters, and many firefighters have poor musculoskeletal health (MSH) that hinder their occupational performance (OP). Establishing the relationship between physical fitness, cardiovascular health (CVH), MSH and OP may add new insight on the most significant factors influencing OP in firefighters, specifically in the City of Cape Town Fire and Rescue Service (CoCTFS), which had not been studied before. Therefore, the purpose of this study was to investigate whether physical fitness, CVH and MSH were associated with OP in firefighters, in the COCTFRS. Methods: This cross-sectional study included 283 full-time firefighters aged 20-65 years from Cape Town, South Africa. A researcher-generated questionnaire was used to collect data on sociodemographic characteristics, lifestyle factors and MSH. Physical measures were used to collect information on physical fitness, CVH, and OP [using a physical ability test (PAT)]. Linear and binary logistic regressions, adjusted for age, sex, height and weekly metabolic equivalent minutes (WMETM), multivariate analysis of covariance (MANCOVA), adjusted for age, sex, height and body mass index (BMI) and backward stepwise regressions were used to investigate the associations between the various constructs. Results: From multivariable analyses, age, lean body mass, body fat percentage (BF%), estimated absolute oxygen consumption (abV̇O2max), grip strength, leg strength, push-ups, sit-ups, WMETM and heart rate variability were associated with PAT completion times (PAT) (all p<0.01). The MANCOVA showed a significant difference between performance categories of the PAT based on physical fitness and CVH (both p<0.001). WMETM, BF%, abV̇O2max, grip strength, leg strength and sit-ups explained the highest proportion (50.5%) of the variation in PAT completion times. Conclusion: Younger, non-obese, fitter and stronger firefighters, with a better CVH status, performed significantly better and were most likely to pass the PAT in firefighters, in Cape Town, South Africa. Firefighters should maintain high levels of physical fitness and a good level of CVH to ensure a satisfactory level of OP.